Urban mobility in São José dos Campos: a construction as a right to come and go or right to the city? - Fochesato, Federica Giovanna; Reschilian, Paulo Romano (Risco - Journal of Architecture and Urbanism, 2021)
This paper aims to analyze the way urban mobility has been built in São José dos Campos, SP, emphasizing the city Municipal Urban Mobility Policy established in 2016. Through an analyzes of the Origin and Destination Survey, the Municipal Urban Mobility Policy of the municipality, and by the use of the territory observation methodological approach, the article will discuss in which ways urban mobility requires a renewed dialogue so that it could be correctly contextualized within urban and regional planning.